194k views
1 vote
Solve 2x^2-11x-6=0 please i need this to pass

User ThingEvery
by
5.4k points

2 Answers

6 votes

Answer:

x = 6 and -0.5

Explanation:

Equation; 2x² - 11x - 6 = 0

a = 2

b = -11

c = -6

Substitute in the values of the equation for the quadratic formula;

-b ±
√(b^2 - 4ac) / 2a

-(-11) ±
√((-11)^2 - 4(2)(-6)) / 2(2)

11 ±
√(121+48) / 4

11 ± 13 / 4

=> 11 + 13 / 4 = 6

=> 11 - 13 = -0.5

So;

x = 6 and -0.5

Hope this helps!

User Ken Hannel
by
5.5k points
3 votes

Answer:

x = -0.5 or 6

Explanation:

→ First find the first set of terms in brackets

( 2x + ? ) ( x - ? )

→ Find 2 numbers which multiply to give -6 and subtract to give -11 when multiplied by 2

( 2x + 1 ) ( x - 6 ) = 0

→ Now solve

x = -0.5 or 6

User Edmund Tam
by
4.7k points